THE STATES LOSSES AT STATE-OWNED ENTERPRISES IN PERSFEKTIF CORRUPTION - Bonto, Zulkifli; Ilmar, Aminuddin; Saidi, Dafar; Sampurno, Slamet (Journal of Humanity, 2015)
State-Owned Enterprises administered by the professional who works with rule and regulation. Steps in the form of profit in money terms, it is not independent of the existence of the risk in the form of the possibility of losses. In carrying out the actions of The State-Owned Enterprises have always been faced with the possibility of obtaining profits or suffer losses. Therefore, the losses that occur in professional decision making should not be casually (not necessarily should) be considered as a deliberate act which is equivalent to committing financial fraudProblem management to State-Owned Enterprises and refines that may give rise to uncertainties in law enforcement corruption, losses arising on a transaction conducted by the perpetrators of State-Owned Enterprises was acts that inflict such losses can be seen as a disadvantage the SOES can be raises the loss of State-Owned Enterprises, considering it as a business entity is seeking a profit, which in its management could be profit or loss depends on how could market mechanisms